Enhanced Magnetic and Dielectric Performance in Fe3O4@Li0.5Cr0.5Fe2O4 Core/Shell Nanoparticles - Mohammed K. Al Turkestani (Nanomaterials)
This study presents the first successful integration of Fe3O4 and Li0.5Cr0.5Fe2O4 into a well-defined core/shell nanostructure through a two-step synthesis that combines co-precipitation and sol–gel auto-combustion methods. Unlike conventional composites, the core/shell design effectively suppresses the magnetic dead layer and promotes exchange coupling at the interface, leading to enhanced saturation magnetization, superior magnetic heating (specific absorption rate; SAR), and improved dielectric properties. Our research introduces a novel interfacial engineering strategy that simultaneously optimizes both magnetic and dielectric performance, offering a multifunctional platform for applications in magnetic hyperthermia, electromagnetic interference (EMI) shielding, and microwave devices.